Melatonin multifaceted pharmacological actions on melatonin receptors converging to abrogate COVID‐19. Issue 1 (26th April 2021) - Reynolds, Jessica L.; Dubocovich, Margarita L.
Abstract: Data indicate that controlling inflammatory responses to COVID‐19 may be as important as antiviral therapies or could be an important adjunctive approach. Melatonin possesses anti‐inflammation, antioxidation, and immune‐enhancing features directly and/or indirectly through its own receptor signaling and is therefore well suited to reduce the severity of COVID‐19. Studies have proposed that melatonin regulates COVID‐19–associated proteins directly through regulation of molecules such as calmodulin (CALM) 1 and CALM 2, calreticulin (CalR), or myeloperoxidase (MPO) and/or indirectly through actions on GPCR (eg, MTNR1A, MTNR1B) and nuclear (eg, RORα, RORβ) melatonin receptor signaling. However, the exact mechanism(s) and doses by which melatonin reduces the severity of COVID‐19 is still open for debate, warranting the need for further testing of melatonin in placebo‐controlled randomized clinical trials for COVID‐19.